1999
DOI: 10.1165/ajrcmb.21.1.3396
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Inhibit Proliferation, Cyclin D1 Expression, and Retinoblastoma Protein Phosphorylation, but Not Activity of the Extracellular-Regulated Kinases in Human Cultured Airway Smooth Muscle

Abstract: We have previously shown that glucocorticoids inhibit mitogen-stimulated proliferation of human cultured airway smooth muscle (ASM) cells. The present study analyzed the effect of glucocorticoids on key regulatory pathways leading to passage of cells through the restriction point of the cell cycle, including those mediated by extracellular-regulated kinases (ERK) 1 and 2; the ERK upstream regulator MAPK kinase (MEK1); cyclin D1 levels; and levels and phosphorylation of retinoblastoma protein (pRb). Fluticasone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 82 publications
8
114
0
1
Order By: Relevance
“…However, no effect of salbutamol was found on cyclin D 1 mRNA, suggesting a post-transcriptional effect on cyclin D 1 , perhaps involving accelerated degradation of the cyclin D 1 protein [159]. In contrast to the lack of effect of glucocorticoids on ERK activity [155], salbutamol prevented ERK activation between 5 min and 8 h following stimulation with a-thrombin, consistent with earlier reports that sustained ERK activation throughout G 1 is necessary for cell cycle traversal [74,75,78]. An additional mechanism that was not investigated in this study, but has been reported previously by these authors [160], was the salbutamol-induced expression of p27 kip1 , a cdk protein inhibitor which prevents phosphorylation of pRb and cell cycle progression by inhibiting cdk activity in the mitogen-activated cyclin D 1 /cdk4 complex.…”
Section: Role Of Phosphoinositide 3-kinase Activation In Proliferationmentioning
confidence: 77%
See 3 more Smart Citations
“…However, no effect of salbutamol was found on cyclin D 1 mRNA, suggesting a post-transcriptional effect on cyclin D 1 , perhaps involving accelerated degradation of the cyclin D 1 protein [159]. In contrast to the lack of effect of glucocorticoids on ERK activity [155], salbutamol prevented ERK activation between 5 min and 8 h following stimulation with a-thrombin, consistent with earlier reports that sustained ERK activation throughout G 1 is necessary for cell cycle traversal [74,75,78]. An additional mechanism that was not investigated in this study, but has been reported previously by these authors [160], was the salbutamol-induced expression of p27 kip1 , a cdk protein inhibitor which prevents phosphorylation of pRb and cell cycle progression by inhibiting cdk activity in the mitogen-activated cyclin D 1 /cdk4 complex.…”
Section: Role Of Phosphoinositide 3-kinase Activation In Proliferationmentioning
confidence: 77%
“…Consistent with the induction of growth-arrest in G 1 and attenuated phosphorylation of pRb, glucocorticoids also reduced levels of a-thrombin-stimulated increases in cyclin D 1 expression. In the same study, dexamethasone was without effect on the activation of ERK by a-thrombin, suggesting that the major effect of glucocorticoids in preventing S phase traversal in these cells was parallel to, or downstream of, ERK activation [155]. However, the events that link activation of ERK to cyclin D 1 expression in airway smooth muscle are unknown, although activated glucocorticoid receptors are known to form a complex with AP-1, perhaps preventing its action on genes required for cell cycle progression to the S phase.…”
Section: Role Of Phosphoinositide 3-kinase Activation In Proliferationmentioning
confidence: 86%
See 2 more Smart Citations
“…Corticosteroids can inhibit the induced release of RANTES, IL-8, GM-CSF and MCP-1 from airway smooth muscle cells in vitro, although they are not effective in inhibiting eotaxin release. In addition, they inhibit thrombin-induced airway smooth muscle proliferation through an inhibition of cyclin protein expression [84,85].…”
Section: Resultsmentioning
confidence: 99%